At the Sandbanks of Critical Communication Studies: Hanno Hardt and the Meandering Mainstreams - McLuskie, Ed (Javnost-The Public, 2013)
The mainstream is winning – again, now as “mainstream version 2.0.” Like word processors and spreadsheets that engineer more than revise, versions and varieties in communication studies extend but rarely revolutionise. Whether 1.x or 2.x, the differences are quibbles on substance and orientation. Communication studies as a field keeps its attentions to shifting technologies, reifies messages a nd audiences, and melts distinctions between communication and control on altars of effects studies and pedagogies. Once defined as a binary battleground – between administrative and critical research, quantitative and qualitative research, etc. – version 2.x takes a lesson from the other side to declare the mainstream an urban legend: multiplicities of coexistence have melted the old binaries if ever there were a basis for the mythology. This dismissal of the critique of the mainstream is remarkable both for its prematurity and its approach to the history of the field’s concepts and approaches to them.